"FROZEN" CONFLICTS OF THE FORMER SOVIET UNION, AS AN EXPRESSION OF THE INSTITUTIONAL CRISIS OF THE EU POLICY - Зельманович, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the main causes of the emergence of "frozen" conflicts in the former Soviet Union are analyzed. It is pointed out that despite the significant and important role played by the EU countries in conflict resolution; the Russian Federation here takes the key position, which tries to use seemingly local conflicts to implement its foreign policy strategy. It is claimed that one of the most urgent and important issues that are on the agenda in international relations now is the issue of the effective resolution of armed conflicts. Since there exists many conflict regions in the world whose conflict for whatever reason cannot be solved. The main attention is paid to the post-Soviet space, where the armed conflicts that emerged as far as the early 90’s in Moldova, Georgia, Azerbaijan, though the conflicts were halted, but continue to exist in the form of the "frozen" confrontation. For a better understanding of these conflicts, the causes of their occurrence, properly, the mechanisms which would contribute to their final resolution: the basic chronological stages of escalation of these conflicts, the main causes of the failure of the international law efforts that have been made to the process of peaceful resolution of these conflicts are revealed in the article. It is pointed out that today the EU countries have appeared not to be ready for the aggressive policy conducted by Russia on the international stage, and the hostages of the policy are the majority of the former Soviet Union countries.